Validation of the Tricuspid Annular Plane Systolic Excursion/Systolic Pulmonary Artery Pressure Ratio for the Assessment of Right Ventricular-Arterial Coupling in Severe Pulmonary Hypertension. (September 2019) - Tello, Khodr; Wan, Jun; Dalmer, Antonia; Vanderpool, Rebecca; Ghofrani, Hossein A.; Naeije, Robert; Roller, Fritz; Mohajerani, Emad; Seeger, Werner; Herberg, Ulrike; Sommer, Natascha; Gall, Henning; et al.
Abstract : Background: The ratios of tricuspid annular plane systolic excursion (TAPSE)/echocardiographically measured systolic pulmonary artery pressure (PASP), fractional area change/invasively measured mean pulmonary artery pressure, right ventricular (RV) area change/end-systolic area, TAPSE/pulmonary artery acceleration time, and stroke volume/end-systolic area have been proposed as surrogates of RV-arterial coupling. The relationship of these surrogates with the gold standard measure of RV-arterial coupling (invasive pressure-volume loop-derived end-systolic/arterial elastance [Ees/Ea] ratio) and RV diastolic stiffness (end-diastolic elastance) in pulmonary hypertension remains incompletely understood. We evaluated the relationship of these surrogates with invasive pressure-volume loop-derived Ees/Ea and end-diastolic elastance in pulmonary hypertension. Methods: We performed right heart echocardiography and cardiac magnetic resonance imaging 1 day before invasive measurement of pulmonary hemodynamics and single-beat RV pressure-volume loops in 52 patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension. The relationships of the proposed surrogates with Ees/Ea and end-diastolic elastance were evaluated by Spearman correlation, multivariate logistic regression, and receiver operating characteristic analyses. Associations with prognosis were evaluated by Kaplan-Meier analysis. Results: TAPSE/PASP, fractional area change/mean pulmonary artery pressure, RV area change/end-systolic area, and stroke volume/end-systolic area but not TAPSE/pulmonary artery acceleration time were correlated with Ees/Ea and end-diastolic elastance. Of the surrogates, only TAPSE/PASP emerged as an independent predictor of Ees/Ea (multivariate odds ratio: 18.6; 95% CI, 0.8–96.1; P =0.08). In receiver operating characteristic analysis, a TAPSE/PASP cutoff of 0.31 mm/mm Hg (sensitivity: 87.5% and specificity: 75.9%) discriminated RV-arterial uncoupling (Ees/Ea <0.805). Patients with TAPSE/PASP <0.31 mm/mm Hg had a significantly worse prognosis than those with higher TAPSE/PASP. Conclusions: Echocardiographically determined TAPSE/PASP is a straightforward noninvasive measure of RV-arterial coupling and is affected by RV diastolic stiffness in severe pulmonary hypertension. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03403868. Abstract : Supplemental Digital Content is available in the text.